Enhancing Circularly Polarized Phosphorescence via Integrated Top-Down and Bottom-Up Approach - Park, Gyurim; Jeong, Dong Yeon; Yu, Seung Yeon; Park, Jong Jin; Kim, Jong H.; Yang, Hoichang; You, Youngmin (Angewandte Chemie - International Edition, 2023)
In the dynamic domain of chiroptical technologies, it is imperative to engineer emitters endowed with circularly polarized luminescence (CPL) properties. This research demonstrates an advancement by employing a combined top-down and bottom-up strategy for the simultaneous amplification of photoluminescence quantum yield (Φ) and the luminescence dissymmetry factor (glum). Square-planar Pt(II) complexes form helical assemblies, driven by torsional strain induced by bis(nonyl) chains. Integration of chiral anions leads these assemblies to prefer distinct helical sense. This arrangement activates the metal-metal-to-ligand charge transfer (MMLCT) transition that is CPL-active, with Φ and |glum| observing an upswing contingent on the charge number and aryl substituents in chiral anions. Utilizing the soft-lithographic micromolding in capillaries technique, we could fabricate exquisitely-ordered, one-dimensional co-assemblies to achieve the metrics to Φ of 0.32 and |glum| of 0.13. Finally, our spectroscopic research elucidates the underlying mechanism for the dual amplification, making a significant stride in the advancement of CPL-active emitters.
Keywords: Bottom up approach; Charge transfer transitions; Chiral anions; Circularly polarized luminescence; Circularly-polarized; Metal to ligand charge transfers; Metal(metal-to-ligand charge-transfer transition; Pt(II) complex; Soft-lithography; Topdown; Circularly Polarized Luminescence; Metal(Metal-to-Ligand Charge-Transfer Transition; Pt(II) Complex; Self-Assembly; Soft Lithography